Adaptation Strategies of Ubrug Theatre on Wayang Nganjor Group Theatre in Pandeglang Regency Banten - Ayunda, Pinta Resty; Haryono, Slamet; Sinaga, Syahrul Syah (Universitas Negeri Semarang, 2025)
This research aims to identify the strategies of Ubrug theatre adaptation in the theatre performance of Wayang Nganjor Group in Pandeglang Regency, Banten Province. It focuses on the Ubrug’s meaning, identity, and elements that are preserved and adapted in the Wayang Nganjor Group theatre, as well as its founder’s perceptions related to the meanings and functions of the adaptation strategies to preserve the traditional values and create new aesthetics in the Wayang Nganjor Group performances. Based on the observation and in-depth interview results with the founders of Wayang Nganjor, it is found that the Wayang Nganjor Group theatre performances are Ubrug improvisational dialogue, structure and narrative of Wayang Golek show as well as the typical rhythm play of Rampak Beduk which are combined creatively by reflecting the cultural interpenetration and creative reconversion from the hybridization of Néstor Garcia Canclini, also shows the space of symbolic negotiation from third space theory by Homi L. Bhabha, where the elements of Ubrug, Wayang Golek, and Rampak Bedug meet and influence each other as well as create new asthetics. The founders of Wayang Nganjor stated that these adaptation strategies are an effort to introduce the art tradition that is more relevant to society’s taste, especially the young generation. It is also an effort to foster awareness towards the local language of Banten and local values in Banten traditional arts. The impact of the research shows that this model of adaptation strategies effectively strengthens the cultural identity, modernizes the traditional performance without losing local identity, and exemplifies the practice model of cultural hybridization that is sustainable and contextual in the preservation of contemporary art.